Direction-changeable lumbar cage versus traditional lumbar cage for treating lumbar spondylolisthesis: A retrospective study. Issue 7 (February 2018) - Zhang, Haiping; Jiang, Yonghong; Wang, Biao; Zhao, Qinpeng; He, Simin; Hao, Dingjun
Abstract : Abstract: Despite the diverse designs for the lumbar interbody fusion cage, there is no consensus on the optimal design to date. The current study aimed to compare the efficacy and complications associated with the direction-changeable and traditional lumbar cages for treating lumbar spondylolisthesis. We conducted a retrospective study including 109 patients with lumbar spondylolisthesis, who were admitted to our hospital from January 2013 to December 2014. The patients were divided into the direction-changeable (group A) and traditional (group B) lumbar cage group. All patients underwent single-level transforaminal lumbar interbody fusion and were followed up for 12 to 24 months. There were 52 cases in group A and 57 cases in group B. Surgery-related parameters, including operation time, bleeding volume, and hospitalization time, were recorded; there was no significant difference between the 2 groups regarding these parameters. The visual analog scale and Oswestry disability index at the last follow-up showed significant improvement compared with preoperative values in both groups ( P < .05). Patients in group A demonstrated more intervertebral space height maintenance postoperatively than patients in group B but the difference was not statistically significant ( P > .05). In group A, complications included 3 cases of nonunion (5.77%) and 1 case of cerebrospinal fluid leakage (1.92%). In group B, complications included 9 cases of nonunion (15.79%) and 1 case of postoperative infection (1.75%). There was a significant difference between both groups in terms of the nonunion rate and total complication rate ( P < .05). The direction-changeable lumbar cage has merits such as a higher bone fusion rate and fewer postoperative complications compared to the traditional lumbar cage.